ANALISIS SWOT POTENSI SUNGAI KARANGAMPEL KIDUL DI KABUPATEN INDRAMAYU - Gita Rakhmawati (Jurnal Teknik dan Science, 2024)
The existence of water is very important for living things. Humans, animals and plants need water to fulfill their daily needs and one of the sources of water can be obtained from rivers. Although Indonesia has many rivers, there are still many rivers that are not maximally utilized due to the lack of public awareness of the importance of river cleanliness. This research aims to find out and recognize the potential of the river by determining the right strategy so that the potential of the river can be known and utilized by the community and the function of the river can return to its original state. The method used in this research is descriptive qualitative method where researchers conducted observations and interviews with people who live around Karangampel Kidul River. The data analysis applied is SWOT analysis (Strength, Weakness, Opportunity, Threat). The results of the SWOT analysis of the potential of the Karangampel Kidul River with coordinates (0.5: 0.5) are in Quadrant I with an S-O strategy (aggressive strategy). There are 3 strategies that can be applied, namely optimizing the implementation of government and regional policies regarding the potential and function of rivers, optimizing human resources as supervisors and actors of mutual cooperation and optimizing rivers to irrigate rice fields and the daily needs of the surrounding community.